Climate change and carbon tax expectations - Michael Hoel (Center for Economic Studies and ifo Institute (CESifo), 2010)
If investors fear that future carbon taxes will be lower than currently announced by policy makers, long-run investments in greenhouse gas mitigation may be smaller than desirable. On the other hand, owners of a non-renewable carbon resource that underestimate future carbon taxes will postpone extraction compared with what they would have chosen had the policymakers been able to commit to the optimal tax path. If extraction costs rise rapidly as accumulated extraction rises, near-term emissions increase as a consequence of a downward bias in the expected future carbon taxes. Whether investments in greenhouse gas mitigation go up or down due to the expectation error depends on the time profile of the returns to the investment.
Keywords: H23; Q30; Q42; Q54; 330; climate change; exhaustible resources; carbon tax; Klimaveränderung; Ökosteuer; Optimale Besteuerung; Fossiler Energieträger; Kohlendioxid; Treibhausgas; Theorie